Effect of Climate Change on Urban Cooperative Societies in Pune District - Karhe Prakash Sukhadev; Roundal Sitaram Rangnath (Revista Electronica de Veterinaria, 2024)
Climate change poses significant challenges to urban cooperative societies, especially in rapidly urbanizing regions like Pune district. This study investigates the effects of climate change on the operations, financial stability, and social cohesion of urban cooperative societies. The research highlights increased operational costs due to fluctuating climatic conditions, infrastructure vulnerability to extreme weather events, and the social impact on marginalized groups within cooperative societies. By analyzing data from cooperative societies across Pune district, the study identifies key trends and challenges, such as rising energy costs, water shortages, and the impact of heatwaves. Furthermore, the research underscores the critical role of cooperative societies in fostering resilience through community-driven adaptation measures. Recommendations emphasize climate-smart infrastructure, enhanced policy support, and capacity building to mitigate climate-related risks.